Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Petani Terhadap Peranan Kelompok Tani Padi Sawah Di Desa Narumonda IV - Andiko Pertanta Simangunsong (SUAN PUBLISHER, 2024)
This study aims to analyze the factors that influence farmers' perceptions of the role of rice farmer groups in the study area. Farmer groups are an important forum for farmer empowerment, but their effectiveness often varies. Farmers' positive perceptions of farmer groups are crucial for the sustainability and success of agricultural programs. This study will use a survey method with a quantitative approach through a questionnaire. Data will be collected from farmers who are members of rice farmer groups. Data analysis will include descriptive analysis, difference tests (if there is a comparison group), and multiple regression analysis to identify influential factors. Predictive results indicate that factors such as extension support, perceived economic benefits, participation in group activities, and socio-economic characteristics of farmers will significantly influence farmers' perceptions. This study is expected to provide strategic input for the government and related parties in efforts to strengthen the role of rice farmer groups